UMP, HTAA Blood Donation Campaign helps save lives - Siti Nurfarmy, Ibrahim (2022)
PEKAN, 1 June 2022 – A total of 187 donors among students and staff of Universiti Malaysia Pahang (UMP) participated in the blood donation campaign at Level 1 Lobby, Student Activity Centre (PAP), UMP Pekan recently.